Vsakdanje življenje Slovencev ob koncu osemdesetih let - Piškurić, Jelka (Studia Historica Slovenica, 2022)
The author presents various aspects of everyday life of Slovenians at the end of the 1980s, particularly the impact of the rapidly rising inflation. At the same time, she outlines different strategies that the people developed to navigate the economic crisis and improve their standard of living. The crisis, both economic and political, also affected public opinion. Dissatisfaction with the increasingly difficult living conditions intensified, and, with it, the criticism of the system. Slovenians became increasingly convinced that Slovenia would have better prospects for development outside the Yugoslav framework. At the turn of the decade, they massively supported political and social changes. The final part of the paper looks at the faster entry of technology into households as well as at a part of the popular culture of the time and the loosening of restrictions regarding the public religious expression.
Keywords: Družbene spremembe; Družbeno življenje in običaji; Inflacija; inflation; manners and customs; political development; Politični razvoj; Slovenia; social change; standard of living; Življenjski standard